Game theory in managerial decision making : Applications to the microfinance industry - Gyulbudaghyan, Kristine; Hořejší, Bronislava, 1955-; Hudík, Marek, 1980-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2020)
The microfinance industry demonstrated fast growth in recent years. On the one hand, small loans are available for a wider audience, especially for those who cannot get access to bank loans. On the other hand, microfinance companies face higher risks of default when they provide unsecured loans to people with low-income levels. This raises a question of optimal design for credit contracts together with the valid criteria for decision making. Game theory proved to be a useful theoretical concept helping managers to make optimal decisions within strategic interactions with other agents.In this thesis, we aim to design an optimal credit agreement for microfinance credit organizations to maximize its expected profit when the future decision of a borrower to repay or not is unknown. We propose incentives for borrowers to exert enough effort for being able to repay debt in the future, which may help to reduce the moral hazard problem for the microfinance credit organization.
Vedoucí práce: Bronislava Hořejší
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses